Potency of Thermoelectric Generator for Hybrid Vehicle - Putra, Nandy; Koestoer, Raldi Artono; Adhitya, Mohammad; Roekettino, Ardian; Trianto, Bayu (Makara Journal of Technology, 2009)
Potency of Thermoelectric Generator for Hybrid Vehicle. Thermoelectric Generator (TEG) has been known as electricity generation for many years. If the temperature difference occurred between two difference semi conductor materials, the current will flow in the material and produced difference voltage. This principle is known as Seebeck effect that is the opposite of Peltier effect Thermoelectric Cooling (TEC). This research was conducted to test the potential of electric source from twelve peltier modules. Then, these thermoelectric generators were applied in hybrid car by using waste heat from the combustion engine. The experiment has been conducted with variations of peltier module arrangements (series and parallels) and heater as heat source for the thermoelectric generator, with variations of heater voltage input (110V and 220V) applied. The experimental result showed that twelve of peltier modules arranged in series and heater voltage of 220V generated power output of 8.11 Watts with average temperature difference of 42.82°C. This result shows that TEG has a bright prospect as alternative electric source.